A comparison of clinical outcomes between radiotherapy and autoimmune cells therapy in non-small cell lung cancer patients. (2016) - Mo, Yongsen; Xin, Xiaoxia; Zhu, Hui; Zhang, Lihong; Li, Jing; Pang, Yan; Li, Jiali
Abstract: Purpose: This study aimed to compare the clinical outcomes of immunotherapy with dendritic cell (DC) vaccine and cytokine-induced killer (CIK) cells with those of radiotherapy in non-small cell lung cancer (NSCLC). Methods: The immunotherapy group included 197 NSCLC patients with stage IIIb–IV disease, loco-regional recurrence, or distant metastasis after surgery who received immunotherapy with DC vaccine and CIK cells. Delayed type hypersensitivity (DTH) skin test results, quality of life (QOL), and safety were analyzed. The well-balanced control group included 192 patients receiving radiotherapy. All patients were followed-up for 569.87±295.52 days for overall survival (OS) analysis using the Kaplan-Meier method. Results: DTH results, QOL, and side effects data were available for 197 patients in the immunotherapy group. One hundred and twenty-one of these (61.42%) developed a positive immune response to immunotherapy evidenced by the DTH skin test, and 180 (91.37%) had improved QOL. Fever was observed in 67 patients (34.01%), insomnia in 86 (43.65%), anorexia in 71(36.04%), joint soreness in 33 (16.75%), and skin rash in seven (3.55%). No server toxicities were observed in the immunotherapy group. Compared with the control group, OS was significantly prolonged in the immunotherapy group ( P =0.000). OS rates at 6, 12, and 18 months were 88.8%, 82.2%, and 79.6% in the immunotherapy group and 73.4%, 64.1%, and59.3% in the control group, respectively. Conclusions: Immunotherapy with DC vaccine and CIK cells might induce an immune response against NSCLC, improve QOL, and offer a survival benefit without severe toxicity in NSCLC patients, compared to radiotherapy.